1994
DOI: 10.1002/eji.1830240537
|View full text |Cite
|
Sign up to set email alerts
|

Processing of viable group A streptococci leads to major histocompatibility complex class II presentation of T cell epitopes from the major protective antigen

Abstract: We have previously mapped major histocompatibility complex (MHC) class II-restricted T cell epitopes of the surface M protein of type 5 group A streptococci (M5) and show here that two out of four epitopes investigated were efficiently processed during incubation of viable streptococci with spleen cells for presentation to M5-specific murine T cell clones. Viable streptococci were processed more efficiently than heat-killed bacteria suggesting that secreted virulence factors of streptococci do not obstruct pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…We studied the mechanisms of uptake of viable S. pyogenes by macrophages for presentation of T cell epitopes M5 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and M5 308-319 from the surface M5 protein to T cell hybridomas. We showed that disruption of actin polymerization blocked presentation of both epitopes from viable S. pyogenes consistent with the complete inhibition of internalization of S. pyogenes as judged from electron microscopy studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We studied the mechanisms of uptake of viable S. pyogenes by macrophages for presentation of T cell epitopes M5 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and M5 308-319 from the surface M5 protein to T cell hybridomas. We showed that disruption of actin polymerization blocked presentation of both epitopes from viable S. pyogenes consistent with the complete inhibition of internalization of S. pyogenes as judged from electron microscopy studies.…”
Section: Discussionmentioning
confidence: 99%
“…J774A.1 macrophages were pulsed with viable S. pyogenes or synthetic peptides in the presence of metabolic inhibitors to study the mechanisms of uptake of S. pyogenes for presentation of two M5 protein T cell epitopes, M5 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and M5 308-319 . First, we treated macrophages with cytochalasin D, which prevents F-actin polymerization, Fig.…”
Section: Uptake Mechanisms For Antigen Processing Of Viable S Pyogenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another epitope, M5/308-3 19/Ad, provided help for induction of peptide-specific antibodies, and was presented from at least three different M types (M5, M6 and M12) of S. pyogenes. In addition, both epitopes were efficiently processed from viable bacteria and the soluble M5 protein for presentation to CD4+ T-cell clones [3,4]. Together this data suggests that these epitopes may be useful for development of streptococcal vaccines.…”
mentioning
confidence: 99%